Chilean copper exports, imports substitution industrialisation and economic growth - Hojman, David E. (The University of Edinburgh, 1980)
This work analyses the character of the relationship between copper exports and Chilean economic growth after World War II. A thorough discussion of qualitative nature both supports the specifications and definitions of a simultaneous equation econometric model, and interprets and qualifies the model's results. Both multiplier analysis and policy simulations support the view that the relation between primary exports and economic growth was negative, basically because exports financed imports competitive with domestic industrial production, a feature whose negative impact upon growth is rooted in particular economic, political, institutional and administrative elements of Chilean society during the relevant period. At least twice, affected industrial groups favoured copper export restrictive policies, challenging the ideological and material foundations of import substitution industrialisation. These results recommend a careful approach to cross-national, multi-country studies, and do not support either simplistic neoclassical models of the relation exports - growth, or naive Chilean versions of the Latin American theory of 'dependencia'. Chapter one poses the principal questions, and the order of presentation of results. Chapter two is a critical survey of previous contributions, that highlights deficiencies and gaps in the academic understanding of the problem. Chapter three discusses the principal factors which ought to be carefully considered in any complete study, or introduced in any relevant econometric model. Chapter four presents this model, structural equations, multiplier analysis, and suggestions for further development. Chapter five deals with policy simulations, and the definition and measurement of an empirical index of conflict between export-oriented and industry-oriented growth styles, and discusses historical instances of industrial support for copper export restrictive policies (an industry-exports feedback effect working through long range political decisions, beyond the limits of the econometric model). Chapter six is the summary and conclusions of the work. Other material is presented in several appendices.

This work analyses the character of the relationship between copper exports and Chilean economic growth after World War II. A thorough discussion of qualitative nature both supports the specifications and definitions of a simultaneous equation econometric model, and interprets and qualifies the model's results.

Both multiplier analysis and policy simulations support the view that the relation between primary exports and economic growth was negative, basically because exports financed imports competitive with domestic industrial production, a feature whose negative impact upon growth is rooted in particular economic, political, institutional and administrative elements of Chilean society during the relevant period.

At least twice, affected industrial groups favoured copper export restrictive policies, challenging the ideological and material foundations of import substitution industrialisation.

These results recommend a careful approach to cross-national, multi-country studies, and do not support either simplistic neoclassical models of the relation exports - growth, or naive Chilean versions of the Latin American theory of 'dependencia'.

Chapter one poses the principal questions, and the order of presentation of results. Chapter two is a critical survey of previous contributions, that highlights deficiencies and gaps in the academic understanding of the problem. Chapter three discusses the principal factors which ought to be carefully considered in any xiii complete study, or introduced in any relevant econometric model. Chapter four presents this model, structural equations, multiplier analysis, and suggestions for further development. Chapter five deals with policy simulations, and the definition and measurement of an empirical index of conflict between export-oriented and industry-oriented growth styles, and discusses historical instances of industrial support for copper export restrictive policies (an industry-exports feedback effect working through long range political decisions, beyond the limits of the econometric model). Chapter six is the summary and conclusions of the work. Other material is presented in several appendices.